2017
DOI: 10.7150/thno.16562
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Multifunctional Magnetic Nanoparticles Loaded with Alpha-Synuclein RNAi Plasmid in a Parkinson's Disease Model

Abstract: Lewy bodies are considered as the main pathological characteristics of Parkinson's disease (PD). The major component of Lewy bodies is α-synuclein (α-syn). The use of gene therapy that targeting and effectively interfere with the expression of α-syn in neurons has received tremendous attention. In this study, we used magnetic Fe3O4 nanoparticles coated with oleic acid molecules as a nano-carrier. N-isopropylacrylamide derivative (NIPAm-AA) was photo-immobilized onto the oleic acid molecules, and shRNA (short h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 50 publications
0
61
0
Order By: Relevance
“…In an attempt to establish a promising treatment for PD, researchers developed a nanocarrier composed of Fe3O4 nanoparticles coated with oleic acid molecules and absorbed short hairpin RNA. It was shown that these superparamagnetic nanoparticles reduced the expression of α-synuclein, suppressed its toxic effects on the cells, and blocked α-synuclein-induced cell death [101]. Another study reported the successful delivery of mesenchymal stem cells (MSCs) and improved neurobehavioral assessment when MSCs were incubated with micrometer-sized iron particles and finally administrated them in a PD mouse model by the way of the intranasal route [102].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…In an attempt to establish a promising treatment for PD, researchers developed a nanocarrier composed of Fe3O4 nanoparticles coated with oleic acid molecules and absorbed short hairpin RNA. It was shown that these superparamagnetic nanoparticles reduced the expression of α-synuclein, suppressed its toxic effects on the cells, and blocked α-synuclein-induced cell death [101]. Another study reported the successful delivery of mesenchymal stem cells (MSCs) and improved neurobehavioral assessment when MSCs were incubated with micrometer-sized iron particles and finally administrated them in a PD mouse model by the way of the intranasal route [102].…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…Gene therapy, which targets the expression of α-synuclein in neurons, is of great concern, and shRNA (short hairpin RNA) has been identified as a promising treatment of PD (Niu et al, 2017). Therefore, researchers coated magnetic Fe 3 O 4 nanoparticles with oleic acid molecules as a nanocarrier and absorbed shRNA.…”
Section: Application Of Iron Oxide Nanoparticles In the Treatment Of Pdmentioning
confidence: 99%
“…Therefore, researchers coated magnetic Fe 3 O 4 nanoparticles with oleic acid molecules as a nanocarrier and absorbed shRNA. They demonstrated that these superparamagnetic nanoparticles can reduce the expression of α-synuclein and thus can prevent the toxic effects on the cell and suppress apoptosis by α-synuclein (Niu et al, 2017). Salama et al (2017) isolated MSCs from C57BL/6 mice, incubated MSCs with micrometer-sized iron oxide (referred to as MPIOs) particles, and finally administrated them in a PD mouse model by the way of the intranasal (IN) route.…”
Section: Application Of Iron Oxide Nanoparticles In the Treatment Of Pdmentioning
confidence: 99%
“…Inorganic particles possess several of the desirable characteristics for nucleic acid transportation, such as biocompatibility, ease of manufacture and storage, as well as ease of controlling their synthesis. To date, numerous studies have been carried out with this type of inorganic particles such as magnetic particles for miRNA release with different applications like cancer [215] and PD [172,216,217].…”
Section: Inorganic Particlesmentioning
confidence: 99%